2011
DOI: 10.22358/jafs/66185/2011
|View full text |Cite
|
Sign up to set email alerts
|

The potential of the wild dog rose (<i>Rosa canina</i>) to mitigate <i>in vitro</i> rumen methane production

Abstract: This study examined the potential of liquid wild dog rose (Rosa canina) seeds oil and solid seeds residue obtained after CO 2 extraction in supercritical conditions to mitigate rumen methane production in vitro. Two experiments were carried out. The substrate comprised of a mixture of meadow hay and barley meal (60:40) for the control diets (CON1 in experiment with oil and CON2 in experiment with residue). The control diets were supplemented up to 5% in dry matter of rose seeds oil (RO) and 5% of rose seeds re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the present experiment, anti-methanogenic activity was found in the plant parts containing from 1.8% to 13.4% of CT, but this effect was not observed in the plant parts containing less than 1.8% of CT. In line with our study, Szumacher-Strabel et al (2011) determined in a ruminal batch culture system study that the seed oil from R. canina reduced methane production.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present experiment, anti-methanogenic activity was found in the plant parts containing from 1.8% to 13.4% of CT, but this effect was not observed in the plant parts containing less than 1.8% of CT. In line with our study, Szumacher-Strabel et al (2011) determined in a ruminal batch culture system study that the seed oil from R. canina reduced methane production.…”
Section: Discussionsupporting
confidence: 87%
“…Tree forage species are also rich in secondary metabolites such as tannins, and are called tanninferous plants. Recent studies have revealed the inhibitory effect of tannins and tanninferous plants on methane emission by ruminants (Dong et al, 2010;Szumacher-Strabel et al, 2011). The phytochemicals, such as tannins and flavonoids, occurring in the structures of Rosa canina (in fruits, seeds, leaves) may reduce ruminal methane production (Woodward et al, 2002; ABSTRACT.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effects of tannins on the populations of methanogens has been carried out both under in vitro and in vivo conditions, however, results were not always unequivocal (Tavendale et al, 2005;Bhatta et al, 2009;Szumacher-Strabel et al, 2011;Cieslak et al, 2012). The range of mitigation of methane production by using tannins is quite broad, from 2% to 58% in comparison with analyzed control groups (Patra and Saxena, 2010a;Bodas et al, 2012), and factors responsible for the mitigation are various, for example, tannin type, plant source.…”
Section: Tanninsmentioning
confidence: 99%
“…This technique is very useful, especially in the estimation of the methanogens population in the rumen (Szumacher-Strabel et al, 2011). The Archaea, which live in the digestion system of ruminants, are very difficult to cultivate in vitro (Garcia et al, 2000).…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%